Comparison of King Vision video laryngoscope (channeled blade) with Macintosh laryngoscope for tracheal intubation using armored endotracheal tubes - Reena (Journal of Anaesthesiology Clinical Pharmacology, 2019)
Background and Aims: During direct laryngoscopy (DL), intubation using armored endotracheal tubes (ETTs) requires help of bougies, stylets, or Magill's forceps, which leads to unnecessary prolongation in the intubation times. The channeled blade of King Vision (KV) video laryngoscope is likely to obviate the need of these equipments for a successful intubation using armored tubes. Material and Methods: After approval from Institutional Ethics Committee and informed consent, 100 patients were randomized to receive endotracheal intubation using armored ETTs either with KV video laryngoscope (VL) channeled blade or with Macintosh laryngoscope. Time to intubation, success rate, time for best glottis view, number of attempts, optimization maneuvers, or complications if any were recorded. Ease of device use was also assessed in terms of insertion, glottis visualization, and intubation. Continuous variables were tested using unpaired t-test and categorical variables with Pearson's Chi-square test. P ≤ 0.05 was considered significant. Result: First attempt success rate was 92% in group KV and 74% in group DL (P = 0.017). Time for successful intubation was less in group KV as compared with group DL (P < 0.0001). Optimization maneuvers such as “BURP” was needed in three patients of group KV and 11 patients of group DL (P = 0.0218). Bougie was needed in 13 patients of group DL and none from group KV (P = <0.001). Ease of device use was similar in the two groups. Conclusion: KVVL offers faster intubating conditions for tracheal intubation requiring armored ETTs in comparison to DL using Macintosh blade.